2016
DOI: 10.1007/978-3-319-33515-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Arsonists or Firefighters? Affectiveness in Agile Software Development

Abstract: Abstract. In this paper, we present an analysis of more than 500 K comments from open-source repositories of software systems developed using agile methodologies. Our aim is to empirically determine how developers interact with each other under certain psychological conditions generated by politeness, sentiment and emotion expressed within developers' comments. Developers involved in an open-source projects do not usually know each other; they mainly communicate through mailing lists, chat, and tools such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The mixed interaction 'polite-impolite' between developers could explain this fact. Ortu et al (2016) showed that when in the presence of impolite or negative comments, the probability of the next comment being impolite or negative was 13% and 25%, respectively. Hence part of the longer time could be spent in trying to shift the exchange of comments toward a (more) polite level.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed interaction 'polite-impolite' between developers could explain this fact. Ortu et al (2016) showed that when in the presence of impolite or negative comments, the probability of the next comment being impolite or negative was 13% and 25%, respectively. Hence part of the longer time could be spent in trying to shift the exchange of comments toward a (more) polite level.…”
Section: Discussionmentioning
confidence: 99%
“…Each contributor of the project can be represented by a node in the graph, and when contributor A comments a pull request created by contributor B, a link is generated from node A to node B. Such direct graph is called Issue Collaboration Network, and Figure 1 shows, as introduced by [29], [31], an example of such a network built using the data from Angular.js. The different colors in the graph represents communities of contributors (calculated using clustering algorithms), while the diameter of each node is proportional to the degree of the node.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, sentiment analysis is receiving increasing attention as part of human factors of SE [18] and has been widely applied in SE tasks [19][20][21][22][23][24][25][26][27][28]. A number of studies applied sentiment analysis in the collaborative online environment (e.g., GitHub, JIRA, Stack Overflow, and App store) presented as follows: Pletea et al [29] mined emotions from security-related discussions around commits and pull request on GitHub, and found that more negative emotions are expressed in securityrelated discussions than in other discussions.…”
Section: B Sentiment Analysis Application In Sementioning
confidence: 99%
“…These SE texts provides a valuable perspective for researchers to detect the developers' satisfaction or difficulties about the project, i.e., their positive or negative sentiments. Thus, to better support software engineering (e.g., [22]) and program comprehension (e.g., [25]) tasks, a growing body of work [19][20][21][22][23][24][25][26][27][28] applies automated sentiment analysis on SE texts from different online tools such as app stores [34][35], Stack Overflow [4,32,36], GitHub [29][30][31], and JIRA [21,22]. These analyses are also favorable in daily SE practice because unlike the traditional approaches [5,6,42], they do not need direct observations or interactions on the developers, thus not likely to hinder them from their assigned development tasks.…”
Section: Introductionmentioning
confidence: 99%